(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides for the production of polymer composite materials based on the recycling of low-density polyethylene waste and the study of its physical and mechanical properties.Elemental sulfur and melamine are used as chemical binders and modifiers in the production of polymer composite materials.In order to increase the fire resistance of composite materials, aluminum oxide was added as a component.The quantitative relationships of the resulting polymer composite materials have been established.Density, which is one of the rheological characteristics of the obtained polymer composite materials, was determined by the method of hydrostatic weighing.According to the results, the components included in recycled polyethylene increase the density of polymer composite materials.t has been established that the increase in density is periodically associated with the quantity, structure and properties of the component included in the polymer composite material.Based on the results obtained, it was established that an increase in the quantitative ratio of the components included in the polymer composite material leads to a parallel increase in the density of the polymer composite material.The components included in the composition of secondary polymer waste, due to their properties, create the formation of heterogeneous phases in the composition of the polymer matrix.However, the formation of chemical bonds with the linear secondary polyethylene matrix, which is the basis of the polymer composite material, is observed.